Genetic dissection of the soybean dwarf mutant dm with integrated genomic, transcriptomic and methylomic analyses - Song, Jian; Wang, Xuewen; Huang, Lan; Li, Zhongfeng; Ren, Honglei; Wang, Jun (Frontiers in Plant Science, 2022)
Plant height affects crop production and breeding practices, while genetic control of dwarfism draws a broad interest of researchers. Dwarfism in soybean (Glycine max) is mainly unexplored. Here, we characterized a dwarf mutant dm screened from ethyl methanesulfonate (EMS) mutated seeds of the soybean cultivar Zhongpin 661(ZP). Phenotypically, dm showed shorter and thinner stems, smaller leaves, and more nodes than ZP under greenhouse conditions. Genetically, whole-genome sequencing and comparison revealed that 210K variants of SNPs and InDel in ZP relative to the soybean reference genome Williams82, and EMS mutagenesis affected 636 genes with variants predicted to have a large impact on protein function in dm. Whole-genome methylation sequencing found 704 differentially methylated regions in dm. Further whole-genome RNA-Seq based transcriptomic comparison between ZP and dm leaves revealed 687 differentially expressed genes (DEGs), including 263 up-regulated and 424 down-regulated genes. Integrated omics analyses revealed 11 genes with both differential expressions and DNA variants, one gene with differential expression and differential methylation, and three genes with differential methylation and sequence variation, worthy of future investigation. Genes in cellulose, fatty acids, and energy-associated processes could be the key candidate genes for the dwarf phenotype. This study provides genetic clues for further understanding of the genetic control of dwarfism in soybean. The genetic resources could help to inbreed new cultivars with a desirable dwarf characteristic.